2019
DOI: 10.1557/jmr.2019.341
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel derived silica/polyethylene glycol hybrids as potential oligonucleotide vectors

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…This method consists of a set of hydrolysis and polycondensation reactions of metal alkoxides that allows the transition of a sol-gel system from a colloidal solution (the 'sol') into a solid 'gel' phase [8]. During this process, a polymer network is formed and the incorporation of a variety of compounds, such as quercetin, is possible [9]. Furthermore, much research has demonstrated that the introduction of polyethylene glycol (PEG) used as an organic additive in the sol-gel methods can protect and change the speed of drug release incorporated into the matrix [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method consists of a set of hydrolysis and polycondensation reactions of metal alkoxides that allows the transition of a sol-gel system from a colloidal solution (the 'sol') into a solid 'gel' phase [8]. During this process, a polymer network is formed and the incorporation of a variety of compounds, such as quercetin, is possible [9]. Furthermore, much research has demonstrated that the introduction of polyethylene glycol (PEG) used as an organic additive in the sol-gel methods can protect and change the speed of drug release incorporated into the matrix [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…During this process, a polymer network is formed and the incorporation of a variety of compounds, such as quercetin, is possible [9]. Furthermore, much research has demonstrated that the introduction of polyethylene glycol (PEG) used as an organic additive in the sol-gel methods can protect and change the speed of drug release incorporated into the matrix [9][10][11]. Regarding the antibacterial properties, it was observed that a minimum of 20 μg/mL of quercetin is sufficient for the inhibition of Staphylococcus aureus and Pseudomonas aeruginosa; a minimum of 300 μg/mL for the inhibition of Proteus vulgaris, and a minimum of 400 μg/mL can inhibit Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silica hybrid gels are among the so-called organic modified silica (ORMOSILs). Nowadays, these materials are being used for multiple applications such as the adsorption of metals in water [ 1 , 2 , 3 ], catalyst support [ 4 , 5 , 6 ], support for luminescent compounds [ 7 , 8 , 9 ], anti-corrosive or fungicide coatings [ 10 , 11 , 12 , 13 ], and biomedicine [ 14 , 15 , 16 , 17 , 18 , 19 ]. The key behind the tunability of the properties of these materials is the synergetic effect that generates the coexistence, at a nanometric scale, of an inorganic skeleton with flexible and functional organic constituents [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sol-gel preparation can be done with a wide variety of precursors, but silica-based carriers are preferred because they are a well-known system, inexpensive, and biodegradable [21]. Moreover, it has also been reported that silica/PEG hybrids allow us to obtain greater elasticity, to avoid particle agglomeration, and to create a network that entraps many kinds of drugs and compounds in only one step [22].…”
Section: Introductionmentioning
confidence: 99%